Performance of Submerged Breakwaters for Coastal Wetland Protection - Hee Min, T.; Sapari, Nasiman; Adnan, Ilyana (2007)

(untitled)
The development and restoration of coastal wetlands has become a critical issue in many regions that long suffer from degradation of coastal wetlands mainly due to development pressures and the effect of sea water rise. Submerged breakwaters have been widely used for the establishment and protection of coastal wetland habitats. In this study, submerged breakwaters that were made up of a plurality of concrete modules, were developed for controlling shoreline erosion in coastal wetlands. Small-scale model tests were conducted to assess the wave transmission characteristics of the modular submerged breakwaters. This study was aimed at quantifying the wave transmission characteristics of the breakwaters with respect to the effects of their widths, faces and configurations. A series of laboratory tests were conducted in cross-sections of the submerged breakwater models using unidirectional regular waves in a wave flume. The influences of wave steepness (Hi/gT2), submergence depth (h/d), breakwater width, faces and configurations, on wave transmission were investigated.